2003
DOI: 10.1177/107110070302400212
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Two Fixation Methods for First Metatarsophalangeal Joint Arthrodesis

Abstract: The stronger and stiffer intramedullary screw technique offers mechanical advantages over the crossed interfragmentary screw technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Multiple retrospective studies have evaluated the results of first MTP joint arthrodesis, 1,2,[4][5][6][7][8][9][11][12][13]16,[20][21][22][23]25,[28][29][30][31] but we are aware of only 1 prospective study 15 evaluating this procedure. Many methods for achieving union have been developed and include sutures, 4 cerclage wire, 12,31 Kirschner wires, 11,13,14,21,28 Steinmann pins, 7,21,22 screws, 2,11,12,20,21,23,24,29 and plates. 1,5-9, 30 Politi et al 27 demonstrated that dome-shaped joint preparation coupled with a dorsal plate and a crossed screw was the most stable construct in synthetic bone models.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple retrospective studies have evaluated the results of first MTP joint arthrodesis, 1,2,[4][5][6][7][8][9][11][12][13]16,[20][21][22][23]25,[28][29][30][31] but we are aware of only 1 prospective study 15 evaluating this procedure. Many methods for achieving union have been developed and include sutures, 4 cerclage wire, 12,31 Kirschner wires, 11,13,14,21,28 Steinmann pins, 7,21,22 screws, 2,11,12,20,21,23,24,29 and plates. 1,5-9, 30 Politi et al 27 demonstrated that dome-shaped joint preparation coupled with a dorsal plate and a crossed screw was the most stable construct in synthetic bone models.…”
Section: Discussionmentioning
confidence: 99%
“…Although the immediate postoperative radiograph was produced without weight–bearing while the late postoperative radiograph was produced with weight-bearing, we do not believe that this could have been the cause of the angular difference observed between them. In our view, this loss (without statistical significance: p > 0.05) occurred because of the fixation with Kirschner wires that was used on some feet, a method that provides less stability 22 , 23 . Kirschner wires were chosen based on the bone quality observed by the surgeon during the operation.…”
Section: Discussionmentioning
confidence: 79%
“…Many techniques for performing arthrodesis of the first metatarsophalangeal joint have been described, with consolidation rates ranging from 80 to 100% 5 , 6 , 7 , 8 , 9 , 10 . Biomechanical studies using different types of fixation have shown that the most stable fixation method is one that combines a traction screw and a dorsal plate 22 , 23 . In evaluating the intermetatarsal angle, we found that the mean was 10 degrees on immediate postoperative radiographs and 10.2 degrees on late postoperative radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…In 10 pairs of cadaver feet, first MP joint arthrodesis was done with cup-and-cone joint surface preparation and fixation with either two crossed 4.0 mm partially-threaded cannulated cancellous screws or a single 6.5 mm partially-threaded intramedullary cancellous lag screw placed parallel to a 1.6 mm Kirschner wire. 59 Load-to-failure testing with a plantar to dorsal load showed that intramedullary fixation was stiffer and stronger than crossed screw fixation. 59…”
Section: Scientific Sessionsmentioning
confidence: 99%
“…59 Load-to-failure testing with a plantar to dorsal load showed that intramedullary fixation was stiffer and stronger than crossed screw fixation. 59…”
Section: Scientific Sessionsmentioning
confidence: 99%